Zaskarżalność wybranych orzeczeń w postępowaniu karnym. Aspekt konstytucyjny - Żurawik, Artur (Kwartalnik Prawa Publicznego, 2012)
Criminal proceeding may deeply affect the rights and freedoms of individuals, even those who has not committed a crime, but even tough – e.g. by mistake – are accused of doing so. A proper and sufficient level of procedural guarantees, protecting individual rights, especially the right of defence, is regarded indispensable in every country ruled by the rule of law. The main aim of the article is to discuss the instruments of the Polish criminal procedure with regard to this problem in the context of guarantees set forth in the Polish Constitution. The author analysis the basic constitutional principles: “audi alteram partem” and the right of appeal, with regard to instruments set forth in Polish Criminal Procedure Code. Some important judgments of the Polish Constitutional Tribunal concerning the procedural rights in criminal proceedings are analysed, too. The author makes critical remarks on Article 325e para. 1 Polish Criminal Procedure Code under which a decision to start preparatory proceedings does not necessarily need any justification. It significantly affects procedural rights of the parties concerned in the proceeding and therefore should – in the author’s opinion – be removed from the Criminal Procedure Code.